Sensitivity distribution of Venturia inaequalis to fenarimol in Québec apple orchards - Carisse, O.; Pelletier, J.R. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
This study was initiated to quantify the baseline sensitivity of apple scab (Venturia inaequalis) to fenarimol, an ergosterol synthesis-inhibiting fungicide. In 1988, 576 monoconidial isolates of Venturia inaequalis were collected from 26 commercial orchards throughout Quebec. Sensitivity to fenarimol was assessed by radial growth inhibition assay. The ED50 values for the 26 orchards ranged from 0.024 to 5.212 (μ g mL-1 with a mean ED50 of 0.156 μg ml-1. Reduced sensitivity, expressed as ED50, was found in three orchards for an overall frequency of 4.51% of isolates. Sensitive isolates had a mean ED50 of 0.079 μg ml-1, whereas isolates with reduced sensitivity had a mean ED50 of 1.714 μ g mL-1, yielding a resistance factor of about 22. Four populations were identified based on the frequency distribution of ED50 values.